Manajemen Nyeri Pascabedah dalam Protokol Enhanced Recovery After Surgery (Eras): Pendekatan Analgesia Multimodal - Putra, I Wayan Merdiyana Eka (Journal of Comprehensive Science, 2025)
Postoperative pain is a complex physiological response resulting from tissue trauma and inflammation, which can increase the risk of postoperative complications and prolong hospitalization. Inadequate pain management is associated with increased neuroendocrine responses, impaired ventilation, and impaired early mobilization. The use of opioids as a single therapy, although effective, often causes side effects that interfere with patient recovery, such as nausea, vomiting, sedation, and postoperative ileus. Enhanced Recovery After Surgery (ERAS) protocols were developed to accelerate recovery, reduce complications, and improve healthcare efficiency. One key component of ERAS is postoperative pain management based on the principle of opioid-sparing, with multimodal analgesia as the primary approach. Multimodal analgesia combines various analgesic agents and techniques with different mechanisms of action to simultaneously reduce pain. This approach has been shown to reduce pain intensity, opioid consumption, accelerate mobilization, and shorten hospitalization. This article aims to examine the role and implementation of multimodal analgesia within the ERAS framework based on the latest scientific literature (2020–2024). Multimodal analgesia is recommended as a standard of modern anesthesiology practice to improve patient postoperative recovery.